Rare earth elements in lake sediments record historic environmental influences from anthropogenic activities - Sainan Wang; Zhuhong Wang; Shilin Gao; Xingyong Zhang; Jie Zeng; Qixin Wu (Ecological Indicators, 2024)
Sediment concentrations of rare earth elements (REEs) can reflect aquatic system impact from anthropogenic activities, especially in small lakes characterized by high sensitivity. However, the literature on REEs in sediment profiles of small lakes is limited, impeding a comprehensive understanding of the historical influence of anthropogenic activities on urban aquatic environments. In this investigation, we examined the spatial distribution and fractionation of REEs in sediments of Aha Lake, a small karst lake. The results reveal that the average REEs contents in surface sediments ranged from 76.88 to 181.38 mg/kg. Light REEs (LREEs) comprised > 80 % of the total REEs in almost all sediments, indicating a distinct enhancement of terrestrial source and influx derived from LREE-rich material. Negative Eu anomalies, weak and positive Ce anomalies in sediments may be attributed to oxidizing conditions. The spatial distribution of ΣREEs in surface sediments display a declining tendency from the lake's border to its center, primarily influenced by human activities. Vertical distributions in most core sediments consistently vary with depth, showing a decrease at 10–20 cm and a higher REEs contents at 20–30 cm. Additionally, distinct UCC-normalized REE distribution patterns are observed at depths of 0–30 cm in core sediments, reflecting contemporary environmental changes at various sampling sites. The impact of coal mining on REE content is found than that of urban development influence only. Moreover, the bivariate (La/Sm)UCC - (La/Yb)UCC plot effectively differentiates the depositional origin of different layers in the core sediments at various locations, such as those associated with coal mining wastewater deposition and urban anthropogenic activities deposition. This study provides valuable insights into historical variations in water environments due to anthropogenic activities, utilizing the sensitive changes in REE levels in small lake sediments.